AMPK negatively regulates RANKL-induced osteoclast differentiation by controlling oxidative stress - Tanaka, Miori; Inoue, Hirofumi; Takahashi, Nobuyuki; Uehara, Mariko (Free radical biology & medicine, 2023)
AMP-activated protein kinase (AMPK) is a crucial energy sensor of cellular metabolism under various metabolic stresses, such as oxidative stress and inflammation. AMPK deficiency increases osteoclast numbers and reduces bone mass; however, the precise mechanisms remain unclear. This study aimed to clarify the mechanistic connection between AMPK and osteoclast differentiation, and the potential role of AMPK in the anti-resorptive effects of several phytochemicals. We found that receptor activator of nuclear factor-kappa B (NF-κB) ligand (RANKL)-induced osteoclast differentiation, osteoclastic gene expression, and activation of mitogen-activated protein kinase (MAPK) and NF-κB were promoted in cells transfected with AMPK siRNA. AMPK knockdown led to defective synthesis of heme oxygenase-1, an antioxidant enzyme, and the upstream mediator, nuclear factor erythroid-2-related factor 2. Furthermore, treatment with N-acetyl-l-cysteine, an antioxidant, abolished osteoclast differentiation and MAPK/NF-κB activation induced by AMPK knockdown. AMPK activators, hesperetin, gallic acid, resveratrol, and curcumin, suppressed osteoclast differentiation via the activation of AMPK. These results suggest that AMPK inhibits RANKL-induced osteoclast differentiation by enhancing antioxidant defense system and regulating oxidative stress. AMPK activation by dietary-derived phytochemicals may be effective for the treatment of bone diseases. [Display omitted] •AMPK knockdown promoted RANKL-induced osteoclast differentiation, osteoclastic gene expression, and MAPK/NF-κB activation in RAW 264.7 cells.•AMPK knockdown led to defective synthesis of HO-1 and Nrf2.•NAC abolished osteoclast formation and MAPK/NF-κB activation induced by AMPK knockdown.•Several phytochemicals suppressed osteoclast differentiation via AMPK.